2020
DOI: 10.1111/hae.14040
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the knowledge, beliefs, behaviours and concerns of Persons with Haemophilia and their carriers in Senegal

Abstract: Haemophilia is a genetic condition affecting 1 out of 10 000 people around the world. The lack of diagnosis is one of the main health challenges for PWH, as only 25% of the global haemophilia patient population have been identified. 1 In Senegal, for example, a study reports a prevalence of 2.3/100 000 male births, accounting for only 11.6% of the expected figure in the country. 2 Very few studies have focused on haemophilia in sub-Saharan Africa, the epidemiological data being mainly obtained from Senegal, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…A culturally adapted educational tool has been developed for Ivory Coast and is available on the site. 20 For all these aspects of diagnosis, education and patient care, the third Edition of “WFH guidelines for the management of hemophilia” is highly valued and of great importance 22 …”
Section: Resultsmentioning
confidence: 99%
“…A culturally adapted educational tool has been developed for Ivory Coast and is available on the site. 20 For all these aspects of diagnosis, education and patient care, the third Edition of “WFH guidelines for the management of hemophilia” is highly valued and of great importance 22 …”
Section: Resultsmentioning
confidence: 99%
“…The knowledge, belief, and practice mode includes three processes of acquiring knowledge, generating beliefs, and forming behaviors. It is a nursing mode to change patients' health-related behaviors [ 6 , 7 ]. The purpose of this study is to estimate the outcome of nursing of health belief-based nursing united with knowledge, belief, and practice mode in patients with gastric cancer, and to provide a basis for the diversity of nursing methods of gastroscopy in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Another such study in Canada identified gaps in the patients' knowledge 11 . A qualitative study (Babington‐Ashaye et al) reported that due to lack of knowledge, people of Senegal attributed haemophilia to various religious beliefs 13 …”
Section: Theoretical Backgroundmentioning
confidence: 99%